Stable Hemodynamics within “No-Touch” Saphenous Vein Graft - Yang, Yan; Jiang, Qin; Sun, Hansong; Tang, Yue; Lv, Feng; Hu, Shengshou (Annals of Thoracic and Cardiovascular Surgery, 2020)
Purpose: To investigate the hemodynamics characteristics of the “no-touch” saphenous vein graft (SVG) conduits by nicardipine intraluminal administration in vivo experiment.Methods: A total of 59 consecutive patients were enrolled and underwent a sequential SVG to three non-left anterior descending (LAD) targets with the average runoff ≤2 mm, 30 with “no-touch” harvest technique (group A) and 29 with conventional preparation (group B). The patients were subject to nicardipine intraluminal injection during off-pump coronary artery bypass grafting (CABG) procedure. The intraoperative flow was measured with the ultrasonic transit time flow meter (TTFM), and the graft patency testified by multi-detector computed tomography (MDCT) angiography, respectively.Results: The baseline blood flow was higher in group A than that in group B (p <0.05). However, the increases in blood flow of SVG conduits in group A were lower than those in group B with 19.7 ± 5.9 vs. 35.4 ± 9.2 mL/min, 14.8 ± 5.6 vs. 23.1 ± 6.8 mL/min, 6.6 ± 2.1 vs. 11.2 ± 4.3 mL/min before the first, second, and third anastomose after nicardipine intraluminal administration, respectively (all p <0.01).Conclusions: No-touch SVGs were associated with higher baseline blood flow and less rises after nicardipine intraluminal administration during off-pump CABG procedure compared with conventional preparation. The no-touch SVGs seemed to be less spastic and well-tolerated on flow dilatation.